Stability of nano-oil by pH control in stationary conditions - Amiruddin, Hilmi; Abdollah, Mohd Fadzli bin; Idris, A.M.; Abdullah, Muhammad Ilman Hakimi Chua; tamaldin, Noreffendy (2015)
The purpose of this study is to investigate the stability of nano-oil by pH control in stationary conditions. The nano-oil was prepared by dispersing an optimal composition of 0.5 vol.% 70 nm hexagonal boron nitride (hBN) nanoparticles in SAE 15W-40 diesel engine oil by sonication technique. Hydrochloric (HCl) acid and Sodium Hydroxide (NaOH) were used as a dispersing agent to determine the stability of the dispersion. The dispersion stability was evaluated by using the sedimentation method with the help of Ultra Violet-Visible (UV-Vis) spectrophotometer. It was demonstrated that the suspension in the alkaline region with a pH value of 11 to 13 was stable over the period of 60 days.